Peran Guru Pendidikan Agama Islam dalam Membentuk Self-Adjustment Santri - Muhammad Nur Yahya; Rahmad Salahuddin (PAI RAFAH, 2024)
This study examines how pesantren, especially Fadlillah pesantren, regarding santri self-adjustment, with an emphasis on the function of Islamic Religious Education (PAI) teachers. Direct observation, documentation study, and in-depth interviews are the approaches used to collect data using phenomenological qualitative methodology. Islamic Education teachers are recognised as very important in helping students face various obstacles today. It is hoped that this research will provide a thorough understanding of the role played by PAI teachers in helping students to adjust to their own lives. This research can also serve as a model for the establishment of Islamic religious teaching and guidance in pesantren. The importance of self-adjustment in the field of psychology provides insight into how people manage obstacles and changes in everyday life. Self-adjustment is usually defined as the ability to control emotions, resolve internal conflicts, and adjust to the social environment. Important phases of adjustment are discussed, including recognising barriers, assessing substitutes, and practising new behaviours. Significant implications for learning and personal growth are also touched upon, emphasising the important role of self-adjustment in enhancing one's psychological and social well-being.